2002
DOI: 10.1038/sj.onc.1205990
|View full text |Cite
|
Sign up to set email alerts
|

Induction of inducible nitric oxide synthase by Epstein-Barr virus B95-8-derived LMP1 in Balb/3T3 cells promotes stress-induced cell death and impairs LMP1-mediated transformation

Abstract: The latent membrane protein 1 (LMP1) of Epstein-Barr virus (EBV) causes cellular transformation and activation of several intracellular signaling events. In this report, we show that BLMP1 (encoded by the LMP1 gene derived from the B95-8 strain of EBV) triggers the expression of inducible nitric oxide synthase (iNOS) in Balb/3T3 fibroblasts. Intriguingly, NLMP1, a natural sequence variant of LMP1 identified in EBV-positive nasopharyngeal carcinoma biopsy, does not similarly induce iNOS expression. BLMP1-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 81 publications
0
15
0
3
Order By: Relevance
“…The detailed regulatory mechanisms by which mitochondrial proteins affect cell cycle progression are still unclear. Many studies have also demonstrated that LMP1 expression increased cellular ROS stress (Yu et al, 2002), but did not lead tumor cells to apoptosis or senescence, which suggested that proteins involved in decreasing cellular ROS stress were activated after LMP1 expression. In this study, we showed that the regulation of the ROS metabolism by LMPIP facilitated the acceleration effect on cell cycle and tumorigenic activity of LMP1.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed regulatory mechanisms by which mitochondrial proteins affect cell cycle progression are still unclear. Many studies have also demonstrated that LMP1 expression increased cellular ROS stress (Yu et al, 2002), but did not lead tumor cells to apoptosis or senescence, which suggested that proteins involved in decreasing cellular ROS stress were activated after LMP1 expression. In this study, we showed that the regulation of the ROS metabolism by LMPIP facilitated the acceleration effect on cell cycle and tumorigenic activity of LMP1.…”
Section: Discussionmentioning
confidence: 99%
“…Although a specific LMP-1 genotypedisease phenotype relationship has not yet been identified (48), NPC-derived LMP-1 is both structurally and functionally different from the LMP-1 derived from the laboratory EBV strain B958 in the following ways: (i) NPC LMP-1 activates NF-B signaling and AP-1 transactivation better than B958 LMP-1 (5,7,15,16,27,33,34), (ii) NPC LMP-1 down-regulates cell immune markers, blocks cell apoptosis, and up-regulates the epidermal growth factor receptor (EGFR) better than B958 LMP-1 (7,8,15,27,33,34,52), and (iii) NPC LMP-1 transforms cells and forms tumors in mice more efficiently than B958 LMP-1 (8,24,28,33,52). Chimeric studies of LMP-1 have mapped some of these functional differences to the carboxy-terminal 30-nucleotide domain encoding amino acids 343 to 352 (28) and transmembrane domain amino acids 85 to 129 (5,34).…”
Section: Epstein-barr Virus (Ebv) Is a Ubiquitous Human Gammaher-mentioning
confidence: 99%
“…Известно, что в индукции iNOS белком LMP1 ключевую роль играют транскрипционные факторы NF-kB и STAT3. Более того, ранее показанные различия в активации iNOS и уровнях внутриклеточной генерации NO между отдельными вариантами LMP1 позволяют нам предположить влияние мутаций LMP1 на этот процесс [20,31]. Для определения значения ограниченного числа замен исследуемых вариантов LMP1 в индукции образования оксида азота, мы анализировали линии Rat-1, постоянно экспрессирующие изучаемые низкодивергентные онкобелки LMP1, а также контрольные варианты LMP1-B95.8 и LMP1-Cao.…”
Section: анализлатентногомембранногобелка1вирусаэпштейна-баррunclassified
“…Различия среди этих вариантов LMP1 также наблюдаются при активации синтеза индуцибельной NO-синтазы (iNOS), и как следствие, продукции оксида азота (NO). NO является свободным короткоживущим радикалом, способным наряду с цитокинами влиять на клеточные эффекторные системы, контролирующие пролиферацию, апоптоз, дифференцировку и устойчивость клетки к стрессовым воздействиям [18][19][20].…”
unclassified